2017
DOI: 10.3389/fpsyg.2017.00207
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Sad People’s Memory Advantage for Faces

Abstract: Sad people recognize faces more accurately than happy people (Hills et al., 2011). We devised four hypotheses for this finding that are tested between in the current study. The four hypotheses are: (1) sad people engage in more expert processing associated with face processing; (2) sad people are motivated to be more accurate than happy people in an attempt to repair their mood; (3) sad people have a defocused attentional strategy that allows more information about a face to be encoded; and (4) sad people scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 145 publications
4
7
0
Order By: Relevance
“…These results extend previous findings, highlighting the improved face identity recognition performance in sad participants Hills et al, 2017) by demonstrating that sad mood leads to improvements in expression identification. Our analyses confirmed that this increase in accuracy is due to sad participants exploring more of the face than happy participants.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results extend previous findings, highlighting the improved face identity recognition performance in sad participants Hills et al, 2017) by demonstrating that sad mood leads to improvements in expression identification. Our analyses confirmed that this increase in accuracy is due to sad participants exploring more of the face than happy participants.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found in a face identity recognition task (Hills, Marquardt, Young, & Goodenough, 2017). Typically, the eyes are the most diagnostic feature of faces for the recognition of identity in White faces (Gold, Sekuler, & Bennett, 2004;Vinette, Gosselin, & Schyns, 2004), as evidenced by event-related potentials that selectively respond to the eyes (Eimer, 1998) and eye-tracking data, showing that the eyes attract more and longer fixations and greater scanning than any other feature (Althoff & Cohen, 1999;Henderson, Falk, Minut, Dyer, & Mahadevan, 2001;Walker-Smith, Gale, & Findlay, 1977), except in sad individuals (Hills et al, 2017;Wu et al, 2012).This highlights the importance of the eyes in identity recognition. Expressions are revealed through more features than just the eyes (e.g., Gosselin & Schyns, 2001;Schyns, Bonnar, & Gosselin, 2002;Smith, Cottrell, Gosselin, & Schyns, 2005).…”
supporting
confidence: 77%
“…Moreover, participants with autism demonstrated similar cross-racial differentiation methods in scanning faces to that observed in healthy individuals [35]. The effect though has not been examined in major depression, while findings in healthy individuals following a sad mood induction did not observe a significant other race effect which was understood as a sad mood being associated with more detailed facial scan patterns that reduce susceptibility to the other race effect [20]. However, the present findings indicate that the other race effect is evident in major depression, in contrast to the findings from the mood induction in healthy participants.…”
Section: Resultsmentioning
confidence: 83%
“…Behavioural evidence of the other race effect in mental health disorders has been reported in schizophrenia and autism, both disorders are associated with pervasive deficits in processing facial expressions [28,35].However, the effect has not been examined in major depression, only in healthy individuals who had undergone a sad mood induction, in which the other race effect was not observed regardless of the emotional facial expression [20]. The findings were understood as due to participants scanning and noting more features of the face during sad mood induction, which suggest that the other race effect would not be expected in major depression.…”
Section: Introductionmentioning
confidence: 99%
“…While featural processing is not considered an expert method for encoding faces (but see Rhodes, Hayward & Winkler, 2006), there is evidence that certain facial features play a more important role in face recognition than others, and this is moderated by participant ethnicity. The eyes are the most diagnostic feature for White participants as revealed through: descriptions (Ellis, Deregowski, &Shepherd , 1975); deficits to recognition through concealment (Gosselin & Schyns, 2001); distortion detection (Hills, Marquardt, Young, & Goodenough, 2017); and eye movements (Althoff & Cohen, 1999;Arizpe, Kravitz, Yovel, & Baker, 2012;. Black participants typically use different features when describing (Ellis et al, 1975) and viewing faces focusing more on the nose and lips than White participants (White participants tend to describe the hair and eye colour more than Black participants).…”
mentioning
confidence: 99%